ANALISIS LANDASAN PENGEMBANGAN KURIKULUM 2013 DALAM PERSPEKTIF FILOSOFIS, YURIDIS, KONSEPTUAL, TEORITIS, DAN EMPIRIS - Arisnelwati Arisnelwati; Risna Oktavia; Ahmad Lahmi (Ensiklopedia of Journal, 2026)
Curriculum is a fundamental component of the education system that determines the direction, content, and quality of learning in schools. This conceptual article aims to analyze the philosophical, juridical, conceptual, theoretical, and empirical foundations that underlie the development of the 2013 Curriculum in Indonesia. Using a library research approach, the study explores the relationship between national education goals and curriculum design principles. Findings indicate that the 2013 Curriculum is supported by philosophical foundations rooted in Pancasila and the 1945 Constitution, juridical legitimacy through educational laws, conceptual frameworks emphasizing competence and scientific learning approaches, theoretical bases derived from modern learning theories, and empirical evidence from educational practice. The article concludes that the integration of these five foundations ensures that the 2013 Curriculum aligns with the vision of national education in shaping holistic, competent, and character-based learners.Keywords: Curriculum Development; Education Philosophy; Juridical Foundation; Learning Theory; 2013 Curriculum